KEANEKARAGAMAN DAN KOMPOSISI IKAN PADA KONDISI PASANG DAN SURUT DI MUARA SUNGAI KELAY KABUPATEN BERAU KALIMANTAN TIMUR - Yudistira, Yudistira; Jusmaldi, Jusmaldi; Hendra, Medi (Jurnal Pendidikan Matematika dan IPA, 2019)
Research on diversity and composition of fish at low tide and high tide condition in downstream Kelay River, District Berau, East Kalimantan is not yet know. The purpose of this research was to determine diversity and composition of fish that present at low tide and high tide condition in downstream Kelay River. In research using purposive sampling method and various sizes gill nets used. Results of this research shows that fish were collected at three locations sampling in downstream Kelay River consist of 14 species, 9 families, and 953 individuals. Based on the number of species, diversity Shannon-Wiener index and dominance index has stable of communities, with high value of diversity index (H'=1.975), high evenness index (E=0.749), and low value of dominance index  (D= 0.173). The number of fish species found at low tide were 11 species and at high tide were 12 species. The similarity index of fish species at low tide and high tide condition were 64.3%.